S40 Phenotypic characterisation of GDF2 mutation carriers in a large cohort of patients with pulmonary arterial hypertension. (December 2018) - Swietlik, EM; Hodgson, J; Hadinnapola, C; Bleda, M; Haimel, M; Church, C; Coghlan, G; Condliffe, R; Corris, PA; Gibbs, JSR; Holden, S; Howard, L; et al.
Abstract : Introduction: A major breakthrough in the understanding the pathobiology of pulmonary arterial hypertension (PAH) was the identification of heterozygous disease-causing mutations in the BMPR2 gene. Recently, mutations were also identified in GDF2, which encodes the ligand for BMPR2 (Gräf S et al., 2018). We hypothesised that patients harbouring mutations in BMPR2 and GDF2 show distinct phenotypes from patients without mutations in previously established disease genes. Methods: A total of 1077 cases of idiopathic and heritable PAH were recruited to NIHR Bioresource-Rare Diseases PAH study and underwent whole genome sequencing. Phenotypic diagnostic information was prospectively collected. Results: Of 1077 patients recruited, 162 had heterozygous mutations in BMPR2 and 10 patients had heterozygous GDF2 mutations, including 2 patients with large deletions at the GDF2 locus not previously described. Plasma GDF2 levels were significantly lower in GDF2 mutation carriers than in healthy controls (79.2 (22.3)vs.202 (35.2);p<0.001). Patients with BMPR2 mutations were younger at diagnosis compared to both GDF2 mutation carriers and individuals without the mutation. There were no differences in functional class. BMPR2 mutation carriers had more severe pulmonary haemodynamics when compared to the other two groups but similar 6 min walking distance (6 MWD). Conversely, GDF2 mutation carriers had the highest 6 MWD. BMPR2 mutation carriers had higher haemoglobin, hematocrit, ALP and bilirubin but lower total protein than the other two groups (table 1). None of the GDF2 mutation carriers had features of hereditary hemorrhagic telangiectasia (HHT) or vascular anomaly syndromes but 3 of BMPR2 mutation carriers had solitary arteriovenous malformations (two pulmonary and one cerebral). Transplant-free survival was no different between groups after adjustment for age and sex, and whether cases were incident or prevalent. Conclusions: We report deletions at the GDF2 locus and reduced plasma GDF2 levels in patients with pathogenic mutations, supporting the functional significance of these mutations. BMPR2 mutation carriers had earlier disease onset, more severe haemodynamics and altered blood test parameters. GDF2 mutation carriers were indistinguishable from PAH patients without disease-causing mutations and showed no features of HHT or vascular anomaly syndromes. On behalf of UK PAH Cohort Study Consortium, NIHR BioResource – Rare Disease Consortium